ARGUMENTASI AGAMA TERHADAP UJARAN KEBENCIAN - Baeti Rohman (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
This study discusses religious arguments against hate speech in multicultural Indonesian society from the point of view of critical theory of race and racism (CTRR/Intersectionality), a phenomenological study that is approached using an open system (infitáhiyyah, opennes) and a multi-dimensionality system (taadud al-Ad, multidimensionality). In any religion, hate speech is strictly not allowed. The rise of hate speech is caused by a weak understanding of intersectionality (the meeting point of race and racism) and the absence of universal religious values at the social practical level. Through a critical theory approach and racism and approached using an open system (infitáhiyyah, opennes) and a multi-dimensionality system (taadud al-Ad, multidimensionality), this phenomenological study emphasizes the importance of bringing together various dimensions of life, especially religion when dealing with social complexities. Even though hate speech is not justified in religion, many do hate speech in the name of religion. This is due to the lack of openness in preaching and the plurality of life seen through one perspective (mono-dimensional). Thus, bringing together differences, openness and multi-dimensionality of perspectives becomes a perception that must be carried out in the context of a multicultural Indonesian society